2021
DOI: 10.3390/jpm11060487
|View full text |Cite
|
Sign up to set email alerts
|

EPR-Effect Enhancers Strongly Potentiate Tumor-Targeted Delivery of Nanomedicines to Advanced Cancers: Further Extension to Enhancement of the Therapeutic Effect

Abstract: For more than three decades, enhanced permeability and retention (EPR)-effect-based nanomedicines have received considerable attention for tumor-selective treatment of solid tumors. However, treatment of advanced cancers remains a huge challenge in clinical situations because of occluded or embolized tumor blood vessels, which lead to so-called heterogeneity of the EPR effect. We previously developed a method to restore impaired blood flow in blood vessels by using nitric oxide donors and other agents called E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 47 publications
4
35
0
Order By: Relevance
“…However, in the last few years, many studies have shown that in human advanced cancers, there is strong heterogeneity of the EPR effect [22]. For example, Ding et al showed that about 90% of human renal tumors have an EPR effect that is significantly heterogeneous [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the last few years, many studies have shown that in human advanced cancers, there is strong heterogeneity of the EPR effect [22]. For example, Ding et al showed that about 90% of human renal tumors have an EPR effect that is significantly heterogeneous [23].…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for the insufficient results of the EPR effect in humans is that human tumors are often diagnosed when they are larger than 3 mm and up to 10 cm or more and such large tumors can present with occluded blood vessels owing to vascular clots and thrombi and consequently partially suppressed blood flow [22]. Islam et al claimed that this blood flow suppression is a key feature of late-stage cancers and, consequently, determines "little or no drug delivery and, therefore, a highly limited EPR effect" after systemic administration of the nanomedicine [22].…”
Section: Introductionmentioning
confidence: 99%
“…A critical issue should be addressed is that the EPR effect is the phenomenon of blood vessels, which is largely dependent on tumor blood flow. While most animal solid tumor models that are rich in blood flow exhibit good EPR effect, many clinical cancers, especially advanced late-stage cancers and refractor cancers, are poor in tumor blood flow due to high coagulation activity and thrombi formation, thus showing unsatisfactory EPR effect [1,2,[10][11][12][13]. Thus, further augmentation of the EPR effect is of great importance and necessity.…”
mentioning
confidence: 99%
“…Thus, further augmentation of the EPR effect is of great importance and necessity. In this regard, we should understand that the EPR effect is not a static phenomenon, it is a dynamic event, which could be enhanced by modulating vascular mediators in tumor such as using angiotensin II, NO/nitroglycerin, and angiotensin II, converting enzyme inhibitors and carbon monoxide [1,2,10,11]. A combination of vascular mediators with nanomedicines may become useful strategies for more effective antitumor nanomedicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation